Manggopoh dalam Bingkai: Weaving the History of Siti Manggopoh Into the Choreography of a Dance Work - Quinta Sari; Venny Rosalina (Universitas Negeri Medan, 2023)
The figure of Siti Manggopoh is an inspirational Minangkabau woman who fought for human rights. The dance work